Adopting SBM-Max and Super SBM-Max to Evaluate the Efficiency of Freight Transportation Arrangement Providers: A Study in Vietnam - Nguyen Thi Kim Lien; Luyen Le Anh (Logi, 2024)
This study aims to evaluate the efficiency of all businesses operating in the Freight Transportation Arrangement (FTA) service provider companies in Vietnam in the years 2016–2022 using the Slacks-Based Measure SBM-Max (SM) and super SBM-Max (SSM) models. The analysis was conducted by calculating the ratio between outputs and inputs in the FTA providers’ operational processes. The projection of the SSM model (Pro) and the Rh indicator were used to propose solutions for the inefficient providers by reducing the excessive inputs and increasing the outputs. The empirical results determined the inefficiency term, efficiency term, and rank for each provider every time. Dinh Vu port was identified as the best FTA provider in Vietnam, ranking first or second throughout the term due to its considerable efforts to perform efficiently. It shall be noted that the use of these models can help FTA providers in Vietnam to identify their strengths and weaknesses in terms of operational efficiency. By implementing the proposed solutions, businesses can improve their performance and ultimately increase their competitive advantage in the market. Further research could explore the effectiveness of these models in other industries or countries to provide deeper insights into their potential applications.